Direct Cd-to-Pb Exchange of CdSe Nanorods into PbSe/CdSe Axial Heterojunction Nanorods - Lee, Dongkyu; Kim, Whi Dong; Lee, Seokwon; Bae, Wan Ki; Lee, Sangheon; Lee, Doh C. (AMER CHEMICAL SOC, 2015)
We report synthesis of PbSe nanorods (NRs) and PbSe/CdSe axial heterojunction NRs via direct Cd-to-Pb cation exchange in CdSe NRs. Use of suited ligand-cation combinations enables the cation exchange while keeping the nanomaterial morphology intact. For example, solvation of Cd2+ using oleylamine (OLA) allows for the cation exchange process, which would not be possible by using oleic acid instead of OLA. A mild cation exchange process, such as mixing Pb-oleate and OLA with CdSe NRs at 130 or 150 degrees C, results in anisotropic replacement of CdSe into PbSe along the < 0001 > direction of wurtzite CdSe, and a partial conversion leads to the formation of heterostructure NRs containing axial CdSe/PbSe heterojunctions. While the cation exchange proceeds at both tips of CdSe NRs, exchange appears to be faster on (000 (1) over bar) planes. Binding energy calculation based on density functional theory reveals that OLA binds strongly to the (000 (1) over bar) facet of CdSe NRs, leading to asymmetric cation exchange. This protocol to convert CdSe nanocrystals directly into PbSe broadens the design range of CdSe/PbSe heterojunction nanomaterials potentially with various morphologies because template CdSe nanocrystals can be prepared in different shapes via colloidal synthesis.
Keywords: CATION-EXCHANGE; LIGAND-EXCHANGE; SEMICONDUCTOR NANOCRYSTALS; EXTINCTION COEFFICIENT; PHASE-TRANSITION; GROWTH; KINETICS; REACTIVITY; CHEMISTRY; WURTZITE